Comparison of Mean and Centroid of Surgically Induced Astigmatism After Standard Cataract Surgery - Kamiya, Kazutaka; Iijima, Kei; Ando, Wakako; Shoji, Nobuyuki (Frontiers in Medicine, 2021)
Purpose: To compare the arithmetic mean of surgically induced astigmatism (M-SIA) and the centroid of surgically induced astigmatism (C-SIA) after standard cataract surgery. Methods: We retrospectively examined two hundred eyes of 100 consecutive patients undergoing bilateral cataract surgery through a 2.8-mm temporal clear corneal incision. We quantitatively measured the magnitude and axis of corneal astigmatism preoperatively and 3 months postoperatively using an automated keratometer (TONOREFF-II, Nidek). The M-SIA and the C-SIA were determined by vector analysis using the Holladay-Cravy-Koch formula. Results: For bilateral data analysis, the magnitude of corneal astigmatism significantly increased from 0.66 ± 0.39 D preoperatively to 0.74 ± 0.64 D postoperatively (paired t test, p=0.012). The M-SIA was 0.50 ± 0.36 D at an axis of 91°. On the other hand, the C-SIA was 0.18 ± 0.60 D at an axis of 97°. For unilateral analysis, we obtained similar outcomes between the right and left eye groups. Conclusions: According to our experience, standard cataract surgery induces corneal astigmatism with-the-rule astigmatic shift of approximately 0.5 D. Although the direction of the C-SIA and the M-SIA showed a similar tendency toward with-the-rule astigmatism, the magnitude of the C-SIA largely decreased to approximately 40% of the M-SIA. It should be noted that the M-SIA was considerably different from the C-SIA, especially when selecting the appropriate toric IOL model and power.